Pentingnya Sains dan Peran Orangtua dalam Pengajaran Sains kepada Anak di Rumah - Wuni Arum Sekar Sari (Journal Ashil: Jurnal Pendidikan Anak Usia Dini, 2021)
The purpose of this study was to determine the importance of teaching science from an early age and the role of parents in teaching science at home, as well as what activities kindergarten children or children aged 5-7 years can study science at home. This happened because during the COVID-19 pandemic, children's schools were encouraged to study at home. As long as children learn at home, many things can be taught to children, one of it is science. This research is a qualitative research, where data is obtained based on the results of literature studies. The results of the study show that the role of parents is very important during learning activities at home. Home is the right place for parents to start exploring science with their children. There are many activities that can be done in teaching science to children, such as asking questions related to science and practicing hand skills. Children learn by doing, by trying new and challenging ideas. This not only happened at school, but parents can also help their children to learn by providing them with a safe and enjoyable science learning experience while at home